Overviewing the Context of Balance of Power to the South China Sea Issue in ASEAN - Welly Puji Ginanjar; Budi Pramono; Priyanto (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
The issue to raise is that the South China Sea has potential resources not only natural resource but also the geostrategy and geopolitics concerns. Geographically, the sea is a waterway for any activities for Asia Pacific countries and part of it is in the region of South East Asia. The tension emerges when China unilaterally claims that the all area of SCS is part of China based on the nine-dash line of historical Chinese fishing ground drawing. The claim definitely prompts protest and condemnation from other countries which claim have the authority in the water as well. As a result, the countries in South East Asia like Malaysia, Vietnam and the Philippines launch their objections against China. This situation ignites another ‘world’s great power’ to intervene. The United States proclaims to form Quadrilateral Security Dialogue consisting U.S., India, Australia and Japan as the members. Indeed, the dialogue’s intention is to confront China’s activity in the waters. Therefore, the inquiry to look at is how should ASEAN play its role to create balance and stability in the waters, or extensively in the South East Asia region? To answer this question, it will observe the issue using the realism paradigm since the issue concerns the state's foreign politics and the effort to create order and stability. Through the realism paradigm, the balance of power will be the concept to address the issue. Thus, it is ASEAN’s effort of the balance of power within the conflict and domination of unilateral interests.